2003
DOI: 10.1002/mrc.1226
|View full text |Cite
|
Sign up to set email alerts
|

NMR and EPR studies of the reaction of nucleophilic addition of (bi)sulfite to the nitrone spin trap DMPO

Abstract: The reaction of the nitrone spin trap 5,5-dimethylpyrroline-N-oxide (DMPO) with sodium (bi)sulfite in aqueous solutions was investigated using NMR and EPR techniques. Reversible nucleophilic addition of (bi)sulfite anions to the double bond of DMPO was observed, resulting in the formation of the hydroxylamine derivative 1-hydroxy-5,5-dimethylpyrrolidine-2-sulfonic acid, with characteristic 1 H and 13 C NMR spectra. The reaction mechanism was suggested and corresponding equilibrium constants determined. The mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 27 publications
(18 reference statements)
6
47
0
Order By: Relevance
“…The DMPOH/CN hydroxylamine is formed in a reversible equilibrium (Supplemental Figure 2), but the signal in the corresponding ESR experiment was clearly identified as artifact [7]. For sulfite, Potapenko showed indirect kinetic evidence for the Forrester-Hepburn artifact in experiments with DMPO [8]. In that publication, the ferricyanide consumption rates of the sulfite oxidation experiment were investigated by means of UV-Vis spectroscopy in the presence and absence of DMPO.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The DMPOH/CN hydroxylamine is formed in a reversible equilibrium (Supplemental Figure 2), but the signal in the corresponding ESR experiment was clearly identified as artifact [7]. For sulfite, Potapenko showed indirect kinetic evidence for the Forrester-Hepburn artifact in experiments with DMPO [8]. In that publication, the ferricyanide consumption rates of the sulfite oxidation experiment were investigated by means of UV-Vis spectroscopy in the presence and absence of DMPO.…”
Section: Discussionmentioning
confidence: 99%
“…In that publication, the ferricyanide consumption rates of the sulfite oxidation experiment were investigated by means of UV-Vis spectroscopy in the presence and absence of DMPO. It was found that in the presence of the spin trap, the ferricyanide reduction was much faster; this increased rate was interpreted as evidence of the Forrester-Hepburn mechanism [8]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations